THE DEVELOPMENT OF VARIETY ART IN UZBEKISTAN: HISTORICAL PATH AND MODERN STATE (Лучшие интеллектуальные исследования, 2025)
Abstract:This article presents scientific insights into the introduction of variety art into Uzbek musical culture, the development of Uzbek national variety art, and the contribution of Uzbek composers and their creative styles in the advancement of this art form.